A Financial Feasibility Study of Fiber Optic Infrastructure in Region A – West Java PT XYZ – A Case Study - Gustinov, Roberto; Murtaqi, Isrochmani (Syntax Literate, 2024)
PT XYZ is a provider of high-quality internet service via fiber optic cables. The company plans to develop a new 500 kilometer fiber optic network in Region A -West Java to serve customer segments business to business (B2B), business to government (B2G), and business to consumer (B2C). This article intends to conduct a financial feasibility study in connection with the development of the project. This research method is qualitative with a case study type. The nature of this research is descriptive. This research was conducted in 2023 at PT XYZ. The types of data used in this research are primary data and secondary data. Primary data collection techniques use in-depth interview techniques; while the secondary data collection technique uses the study-desk method. The data analysis method in this article uses a financial feasibility study, with five financial analysis tools, namely NPV, IRR, DPP, PI, and WACC. The research results show that the development of fiber optic infrastructure in Region A by PT XYZ is feasible based on NPV, IRR, DPP, PI and WACC calculations. The implication of this research is, for the management of PT XYZ, to make it even more feasible, steps should be taken in accordance with controlling action, both controlling revenue and controlling expenditure.